Effectiveness of Batang Regional Regulation Number 4 of 2015 Concerning Eradication of Prostitution in Prostitution Localization Area of Karangasem Village, Batang District - Erni Atna; Uswatun Khasanah (Faculty of Sharia, State Islamic University KH. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
This study aims to determine the effectiveness of Regional Regulation Number 4 of 2015 concerning the Eradication of Prostitution in Batang Regency and to find out the legal consequences. The case raised in this study is a localization case that occurred in Karangasem Village, Batang Regency. Prostitution is an activity that violates religious norms and state regulations, this is because it has a negative impact on oneself and many people. Cases of prostitution are still rife in Batang Regency even though Batang Regency is a place where religious values ​​and culture of decency are highly guarded. This is what makes the Batang district government act to tackle, eradicate, bring order and close these dirty businesses. Due to the existence of the prostitution place, it has violated several regional regulations, namely Regional Regulation No. 4 of 2015 concerning the Eradication of Prostitution. The existence of these regional regulations reflects that the local government is committed to eradicating prostitution but indeed enforcement is still minimal, judging by the fact that there are still many stalls or places that are used as prostitution practices. This type of research is empirical juridical with a statutory research approach. Sources of data in this study are primary data and secondary data obtained through observation, interviews, and documentation. While the analysis technique used by the author is a qualitative analysis technique. The results of the research on public legal awareness of the negative impact of prostitution are very low. The legal consequences of the lack of maximum legal awareness of the community towards the negative impact of prostitution are the rampant practice of prostitution, the failure of the laws made to tackle prostitution cases. It would be better if the local government to the village government made regular education so that the suppression of the number of prostitution decreases.